Polymer-coated solid waste-based phase change material, preparation method thereof and application of polymer-coated solid waste-based phase change material in temperature self-adjusting asphalt

By adding polymer-wrapped solid waste-based phase change materials to asphalt, the disease problems caused by temperature sensitivity of asphalt pavement are solved, temperature self-regulation is achieved, pavement life and durability are extended, and the development of environmentally friendly and sustainable road asphalt varieties are promoted.

CN119912909AActive Publication Date: 2025-05-02GAODE HIGHWAY CONSTR (DEZHOU) CO LTD +3
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510084208.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-05-02
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

Due to temperature sensitivity, asphalt pavement is prone to soften at high temperatures and brittle and hard at low temperatures, resulting in diseases such as ruts and thermal cracks, affecting the life and durability of the pavement.

Method used

The polymer-encapsulated solid waste-based phase change material is prepared by mixing the phase change material, carrier material and shell material in a specific proportion, and by mechanical grinding, calcining and vacuum impregnation, etc., to form a polymer-coated solid waste-based phase change material and add it to the asphalt to achieve temperature self-regulation.

Benefits of technology

Effectively reduce the damage to asphalt pavement by too high or too low temperatures, improve the self-regulation ability of pavement temperature, extend the service life and durability of asphalt pavement, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249639280000151
    Figure BDA0005249639280000151
  • Figure BDA0005249639280000161
    Figure BDA0005249639280000161
Patent Text Reader

Abstract

The invention discloses a polymer-coated solid waste-based phase change material, a preparation method thereof and application of the polymer-coated solid waste-based phase change material in temperature self-adjusting asphalt, and belongs to the technical field of asphalt pavement materials. The polymer-coated solid waste-based phase change material is prepared from the following raw materials in parts by weight: 70-90 parts of a phase change material, 20-35 parts of a solid waste-based carrier material and 10-25 parts of a shell material. The polymer-coated solid waste-based phase change material is mixed with a dispersing agent and petroleum asphalt to prepare the temperature self-adjusting asphalt. After the temperature self-adjusting asphalt is paved on a pavement and officially serves, the phase change material fully utilizes the characteristics of porosity and supporting property of the solid waste-based material, meanwhile, the sustainable resource utilization way is expanded, and the influence on the environment and the waste of resources are reduced through integration; the material can be subjected to phase change reaction when the pavement is heated or cooled, so that heat is absorbed or released, self-regulation of the road temperature is realized, the service life of the asphalt pavement is prolonged, and the durability of the asphalt pavement is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of asphalt pavement materials, and in particular to a polymer-coated solid waste-based phase change material, a preparation method thereof, and an application thereof in temperature self-regulating asphalt. Background Art

[0002] Road infrastructure, especially highways, as the core component of road infrastructure, is responsible for connecting cities, transporting goods and providing emergency services, and plays an extremely important role in the development of global transportation. Asphalt pavement, as the main type of pavement for high-grade highways, is widely used due to its advantages such as easy maintenance, smooth driving, high safety, low noise, recyclability and relatively low cost. However, as one of the main components of asphalt pavement, asphalt is a temperature-sensitive material. It easily softens at high temperatures and becomes brittle and hard in the low temperature range. Due to this temperature sensitivity, asphalt pavement is mainly affected by two major diseases during its service life, namely rutting caused by high temperature and traffic loads and thermal cracking under low temperature conditions, which causes damage to the asphalt pavement, especially in areas with drastic temperature changes. Therefore, improving the variety of asphalt is crucial to maintaining the quality of asphalt pavement and extending its life.

[0003] With the development of global road infrastructure, the road materials industry has put forward higher quality requirements for the elasticity and durability of asphalt pavement. Phase change materials, also known as phase change energy storage materials, are a special class of materials. They can change their physical state within a certain temperature range, that is, the phase change temperature range, such as from solid to liquid or from liquid to solid, and absorb, store or release a large amount of heat in the form of latent heat, while their own temperature remains unchanged. This characteristic gives phase change materials unique thermal energy storage and temperature regulation control capabilities, making them have broad application potential in many fields, including but not limited to solar energy utilization, power peak regulation, waste heat recovery, seasonal heat storage and cold storage, food preservation, building insulation and heat preservation, electronic device thermal management, agriculture and textile clothing. However, although phase change materials have been widely used in many of the above-mentioned fields, their potential applications in the field of road transportation have not yet been fully studied and developed.

[0004] In order to improve the performance of asphalt pavements and reduce temperature-induced damage, researchers have been looking for new methods. Phase change materials, as a potential modifier, can be added to asphalt binders to reduce thermal deformation of asphalt pavements. In asphalt pavements, phase change materials usually absorb heat at high temperatures, thereby reducing the pavement temperature, and release heat at low temperatures, which helps to increase the pavement temperature and alleviate the formation of cold cracks. However, adding phase change materials directly to asphalt may cause problems, such as affecting the colloidal stability and high-temperature performance of asphalt. Therefore, during the addition process, the performance and stability of phase change materials need to be comprehensively considered to achieve their optimal effect. Summary of the invention

[0005] The purpose of the present invention is to provide a polymer-coated solid waste-based phase change material, a preparation method thereof, and an application in temperature self-regulating asphalt to solve the above-mentioned problems. After the temperature self-regulating asphalt is paved on the road surface and officially put into service, the polymer-coated solid waste-based phase change material therein can reduce the damage to the asphalt pavement caused by excessively high or low temperatures, thereby improving the service life and durability of the asphalt pavement.

[0006] To achieve the above-mentioned purpose, the present invention discloses a polymer-coated solid waste-based phase change material, which is composed of a phase change material, a carrier material and a shell material. The above-mentioned raw materials are calculated by weight as follows: 70-90 parts of phase change material, 20-35 parts of carrier material, and 10-25 parts of shell material.

[0007] Preferably, the carrier material is any one of red mud, diatomaceous earth, steel slag and furnace slag, and the shell material is any one of epoxy resin, vinyl resin and amino-modified phenolic resin.

[0008] Preferably, the phase change material is any one of polyethylene glycol 2000, polyethylene glycol 4000, polyethylene with a carbon chain length of 30-40, and paraffin with a carbon chain length of 25-30.

[0009] The present invention also provides a method for preparing the above-mentioned polymer-coated solid waste-based phase change material, comprising the following steps:

[0010] (1) placing the solid waste-based materials in an oven to fully dry;

[0011] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 30-70 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material;

[0012] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0013] (4) introducing the melted phase change material in step (3) into the active solid waste-based powder container in step (2), mixing, and vacuum impregnating in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C., and impregnating for 4-6 hours;

[0014] (5) placing the mixture in (4) in a shearing device, stirring at a speed of 150 r / min for 5-10 minutes, adding the shell material three times, and continuing to stir for 10 minutes;

[0015] (6) The mixture in (5) is placed in a drying oven and dried for 2-4 hours, and sheared into particles using a shearing machine with a fineness of 10-20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0016] The present invention provides the use of the above-mentioned polymer-coated solid waste-based phase change material in temperature self-regulating asphalt. The polymer-coated solid waste-based phase change material is mixed with a dispersant and petroleum asphalt in a weight ratio of (5-20): (0.4-0.9): 100 to obtain a temperature self-regulating asphalt.

[0017] Preferably, the petroleum asphalt is 70# petroleum asphalt.

[0018] Preferably, the dispersant is any one of polyvinyl alcohol, fatty alcohol polyoxyethylene ether and polyoxyethylene.

[0019] Preferably, the preparation of the temperature self-regulating asphalt comprises the following steps:

[0020] S1. Heat petroleum asphalt to 130-150℃ until it melts;

[0021] S2, introduce the petroleum asphalt in S1 into the shearing device and stir at a speed of 200r / min for 3-5 minutes;

[0022] S3, add the dispersant into the shearing device, maintain 130-150°C, and stir at a speed of 200r / min for 10 minutes;

[0023] S4. Add the polymer-coated solid waste-based phase change material into the dispersant of S3, and continue stirring at a speed of 400 r / min for 15-20 minutes to obtain a temperature self-regulating asphalt.

[0024] In industrial production, solid waste-based materials are a typical industrial solid waste, containing a large amount of red mud and other valuable components. The direct stacking or treatment of solid waste-based materials will cause harm to the environment. However, it has significant characteristics as a carrier material, including the ability to present a porous morphology and significant high temperature tolerance. The appropriate addition can also improve the performance of asphalt. This phase change asphalt encapsulates the phase change material in a carrier material, and then adds these carrier materials to the asphalt. This method helps prevent the leakage of the phase change material and can achieve a uniform dispersion of the phase change material in the asphalt, thereby improving performance and stability. On the other hand, solid waste-based materials as industrial waste represent a sustainable resource utilization approach. Their integration reduces the impact on the environment and the waste of resources, and invents an environmentally friendly and sustainable road asphalt variety.

[0025] Therefore, the present invention has the following beneficial effects:

[0026] (1) The polymer-coated solid waste-based phase change material of the present invention develops the application of phase change materials in the field of road transportation, and the polymer coating effectively prevents leakage of the phase change material, realizes uniform dispersion of the phase change material in asphalt, thereby improving the temperature regulation performance.

[0027] (2) In industrial production, solid waste-based materials are a typical type of industrial solid waste, and direct stacking or treatment will cause harm to the environment. Full utilization reduces environmental damage and resource waste, and achieves sustainable resource utilization; solid waste-based materials are porous, and grinding them and calcining them can connect their internal gaps, increase their specific surface area, and thus load more phase change materials; when phase change occurs, the porous characteristics of solid waste-based materials can serve as a skeleton support, which can enhance the performance of asphalt itself.

[0028] (3) The present invention adopts advanced polymer coating technology to composite solid waste materials with phase change materials, and enhances the structural stability of the materials through polymer coating; the coating effectively reduces the sensitivity of asphalt to temperature, reduces the occurrence of diseases, and improves the road surface's temperature self-regulation ability, while also greatly improving the road surface's high-temperature rutting resistance and low-temperature cracking resistance.

[0029] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further illustrated by examples below.

[0031] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0032] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0033] Example 1

[0034] This embodiment provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0035] The polymer-coated solid waste-based phase change material consists of a phase change material, a carrier material and a shell material. 80 parts of the phase change material PEG-4000, 25 parts of the carrier material red mud and 15 parts of the shell material epoxy resin are weighed by weight.

[0036] The solid waste-based phase change asphalt was prepared according to the following steps:

[0037] (1) placing the solid waste-based materials in an oven to fully dry;

[0038] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material;

[0039] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0040] (4) introducing the molten material in step (3) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0041] (5) placing the mixture in (4) in a shearing device and stirring at a speed of 150 r / min for 8 minutes, adding the shell material three times, and continuing stirring for 10 minutes;

[0042] (6) The mixture in (5) was placed in a drying oven and dried for 3 hours, and sheared into particles using a shearing machine with a fineness of 20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0043] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0044] (1) Heat 70# petroleum asphalt until it melts;

[0045] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0046] (3) Add rosin resin into the shearing device, maintain 150° C., and stir at a speed of 200 r / min for 10 minutes;

[0047] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0048] Example 2

[0049] This embodiment provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0050] Weigh 80 parts of phase change material, 30 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-4000; the carrier material is red mud; and the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0051] (1) placing the solid waste-based materials in an oven to fully dry;

[0052] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material;

[0053] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0054] (4) introducing the molten material in step (3) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0055] (5) placing the mixture in (4) in a shearing device, stirring at a speed of 150 r / min for 10 minutes, adding the shell material three times, and continuing to stir for 10 minutes;

[0056] (6) The mixture in (5) was placed in a drying oven and dried for 4 hours, and sheared into particles using a shearing machine with a fineness of 20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0057] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0058] (1) Heat 70# petroleum asphalt until it melts;

[0059] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0060] (3) Add rosin resin into the shearing device, maintain 130-150° C., and stir at a speed of 200 r / min for 10 minutes;

[0061] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0062] Example 3

[0063] This embodiment provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0064] Weigh 80 parts of phase change material, 25 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-2000; the carrier material is red mud; the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0065] (1) placing the solid waste-based materials in an oven to fully dry;

[0066] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material;

[0067] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0068] (4) introducing the molten material in step (3) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 4 hours;

[0069] (5) placing the mixture in (4) in a shearing device, stirring at a speed of 150 r / min for 5-10 minutes, adding the shell material three times, and continuing to stir for 10 minutes;

[0070] (6) The mixture in (5) was placed in a drying oven and dried for 4 hours, and sheared into particles using a shearing machine with a fineness of 15 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0071] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0072] (1) Heat 70# petroleum asphalt until it melts;

[0073] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0074] (3) Add rosin resin into the shearing device, maintain 145°C, and stir at a speed of 200 r / min for 10 minutes;

[0075] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0076] Example 4

[0077] This embodiment provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0078] Weigh 80 parts of phase change material, 30 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-2000; the carrier material is red mud; the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0079] (1) placing the solid waste-based materials in an oven to fully dry;

[0080] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material;

[0081] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0082] (4) introducing the molten material in step (3) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0083] (5) placing the mixture in (4) in a shearing device and stirring at a speed of 150 r / min for 7 minutes, adding the shell material three times, and continuing stirring for 10 minutes;

[0084] (6) The mixture in (5) was placed in a drying oven and dried for 3 hours, and sheared into particles using a shearing machine with a fineness of 15 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0085] The above polymer-coated solid waste-based phase change material is mixed with styrene resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0086] (1) Heat 70# petroleum asphalt until it melts;

[0087] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 4 minutes;

[0088] (3) Add styrene resin into the shearing device, maintain 140° C., and stir at a speed of 200 r / min for 10 minutes;

[0089] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 18 minutes, thereby obtaining temperature self-regulating asphalt.

[0090] Comparative Example 1

[0091] This comparative example provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0092] Weigh 50 parts of phase change material, 25 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-4000; the carrier material is red mud; the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0093] (1) placing the solid waste-based materials in an oven to fully dry;

[0094] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder;

[0095] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0096] (4) introducing the molten material in step (3) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0097] (5) placing the mixture in (4) in a shearing device and stirring at a speed of 150 r / min for 8 minutes, adding the shell material three times, and continuing stirring for 10 minutes;

[0098] (6) The mixture in (5) was placed in a drying oven and dried for 3 hours, and sheared into particles using a shearing machine with a fineness of 20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0099] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0100] (1) Heat 70# petroleum asphalt until it melts;

[0101] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0102] (3) Add rosin resin into the shearing device, maintain 150° C., and stir at a speed of 200 r / min for 10 minutes;

[0103] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0104] Comparative Example 2

[0105] This comparative example provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0106] Weigh 80 parts of phase change material, 30 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-4000; the carrier material is clay; the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0107] (1) placing the carrier material in an oven to fully dry;

[0108] (2) The dried carrier material is mechanically ground into powder with a fineness of 50 mesh; then calcined and cooled to room temperature to obtain an active powder;

[0109] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0110] (4) introducing the molten material in step (3) into a powder container and mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0111] (5) placing the mixture in (4) in a shearing device, stirring at a speed of 150 r / min for 10 minutes, adding the shell material three times, and continuing to stir for 10 minutes;

[0112] (6) The mixture in (5) was placed in a drying oven and dried for 4 hours, and sheared into particles using a shearing machine with a fineness of 20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0113] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0114] (1) Heat 70# petroleum asphalt until it melts;

[0115] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0116] (3) Add the rosin resin dispersant into the shearing device, maintain the temperature at 130-150° C., and stir at a speed of 200 r / min for 10 minutes;

[0117] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0118] Comparative Example 3

[0119] This comparative example provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0120] Weigh 80 parts of phase change material and 25 parts of carrier material by weight. The phase change material is PEG-2000; the carrier material is red mud. Prepare solid waste-based phase change asphalt according to the following steps:

[0121] (1) placing the solid waste-based materials in an oven to fully dry;

[0122] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder;

[0123] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0124] (4) Introducing the molten material into the solid waste-based powder container and mixing, vacuum impregnating in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60 ° C for 4 hours;

[0125] (5) The mixture in (4) was placed in a drying oven and dried for 4 hours, and sheared into particles using a shearing machine with a fineness of 15 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0126] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0127] (1) Heat 70# petroleum asphalt until it melts;

[0128] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0129] (3) Add rosin resin into the shearing device, maintain 145°C, and stir at a speed of 200 r / min for 10 minutes;

[0130] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0131] Comparative Example 4

[0132] This comparative example provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0133] Weigh 80 parts of phase change material, 30 parts of carrier material, and 15 parts of shell material by weight. The phase change material is PEG-2000; the carrier material is red mud; the shell material is epoxy resin. Prepare solid waste-based phase change asphalt according to the following steps:

[0134] (1) placing the solid waste-based materials in an oven to fully dry;

[0135] (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 50 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder;

[0136] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0137] (4) introducing the molten material in step (2) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0138] (5) placing the mixture in (3) in a shearing device and stirring at a speed of 150 r / min for 7 minutes, adding the shell material three times, and continuing stirring for 10 minutes;

[0139] (6) The mixture in (4) was placed in a drying oven and dried for 3 hours, and sheared into particles using a shearing machine with a fineness of 15 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0140] The above polymer-coated solid waste-based phase change material is mixed with styrene resin and 70# petroleum asphalt at a ratio of 10:0.2:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0141] (1) Heat 70# petroleum asphalt until it melts;

[0142] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 4 minutes;

[0143] (3) Add styrene resin into the shearing device, maintain 130-150° C., and stir at a speed of 200 r / min for 10 minutes;

[0144] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 18 minutes, thereby obtaining temperature self-regulating asphalt.

[0145] Comparative Example 5

[0146] This comparative example provides a method for preparing a polymer-coated solid waste-based phase change material, as shown below:

[0147] The polymer-coated solid waste-based phase change material is composed of a phase change material, a carrier material and a shell material. 80 parts of the phase change material, 25 parts of the carrier material and 15 parts of the shell material are weighed by weight. The phase change material is PEG-4000; the carrier material is red mud; and the shell material is epoxy resin. The solid waste-based phase change asphalt is prepared according to the following steps:

[0148] (1) placing the solid waste-based materials in an oven to fully dry;

[0149] (2) Mechanically grinding the dried solid waste-based materials into solid waste-based powders, with the fineness maintained at 50 meshes;

[0150] (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted;

[0151] (4) introducing the molten material in step (2) into a solid waste-based powder container for mixing, and performing vacuum impregnation in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C. for 5 hours;

[0152] (5) placing the mixture in (3) in a shearing device and stirring at a speed of 150 r / min for 8 minutes, adding the shell material three times, and continuing stirring for 10 minutes;

[0153] (6) The mixture in (4) was placed in a drying oven and dried for 3 hours, and sheared into particles using a shearing machine with a fineness of 20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

[0154] The above polymer-coated solid waste-based phase change material is mixed with rosin resin and 70# petroleum asphalt at a ratio of 10:0.5:100 to synthesize a temperature self-regulating asphalt. The specific steps are as follows:

[0155] (1) Heat 70# petroleum asphalt until it melts;

[0156] (2) introducing the 70# petroleum asphalt prepared in step (1) into a shearing device and stirring at a speed of 200 r / min for 5 minutes;

[0157] (3) Add rosin resin into the shearing device, maintain 150° C., and stir at a speed of 200 r / min for 10 minutes;

[0158] (4) Adding the polymer-coated solid waste-based phase change material to the mixture of step (3), stirring at a speed of 400 r / min for 20 minutes, thereby obtaining temperature self-regulating asphalt.

[0159] In order to test the performance of the temperature self-regulating asphalt synthesized from the polymer-coated solid waste-based phase change material prepared in Examples 1-4 and Comparative Examples 1-5, the test method in the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011) was used for testing, and the test results are shown in Table 1:

[0160] Table 1 Test results of temperature self-regulating asphalt

[0161]

[0162]

[0163] Through the above test results, it can be concluded that: when the carrier material content is 30 parts, the high and low temperature performance of asphalt is better (Example 1, Example 2), the phase change material PEG-4000 has a greater phase change potential than PEG-2000 (Example 1, Example 3); when the phase change material content is 80 parts, the phase change potential is greater, and the temperature self-regulation ability is stronger (Example 1, Comparative Example 1); the use of solid waste-based material red mud can well improve the high and low temperature performance of asphalt, and store more phase change materials, and the temperature self-regulation ability is stronger (Example 2, Comparative Example 2); the use of polymer coating can reduce the leakage of phase change materials and prevent the reduction of the temperature self-regulation ability of asphalt (Example 3, Comparative Example 3); increasing the amount of dispersant can ensure that the phase change material is more evenly dispersed, so that the utilization rate of the phase change material is higher and the phase change potential is greater (Example 4, Comparative Example 4); the calcination of solid waste-based materials helps to connect the internal gaps and increase its specific surface area, so that more phase change materials can be loaded and the phase change potential of asphalt is improved (Example 1, Comparative Example 5).

[0164] Therefore, the present invention provides a polymer-coated solid waste-based phase change material, a preparation method thereof, and an application in temperature self-regulating asphalt. After the temperature self-regulating asphalt is paved on the road surface and officially put into service, the polymer-coated solid waste-based phase change material therein can reduce the damage to the asphalt pavement caused by excessively high or low temperatures, thereby improving the service life and durability of the asphalt pavement.

[0165] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A polymer-coated solid waste-based phase change material, characterized in that: The polymer-wrapped solid waste-based phase change material is composed of a phase change material, a carrier material and a shell material, and the above raw materials are calculated by weight as follows: 70-90 parts of phase change material, 20-35 parts of carrier material, and 10-25 parts of shell material.

2. The polymer-coated solid waste-based phase change material according to claim 1, characterized in that: The carrier material is any one of red mud, diatomaceous earth, steel slag and furnace slag, and the shell material is any one of epoxy resin, vinyl resin and amino-modified phenolic resin.

3. The polymer-coated solid waste-based phase change material according to claim 1, characterized in that: The phase change material is any one of polyethylene glycol 2000, polyethylene glycol 4000, polyethylene with a carbon chain length of 30-40, and paraffin with a carbon chain length of 25-30.

4. A method for preparing a polymer-coated solid waste-based phase change material as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) placing the solid waste-based materials in an oven to fully dry; (2) The dried solid waste-based material is mechanically ground into a solid waste-based powder with a fineness of 30-70 mesh; then the solid waste-based powder is calcined and cooled to room temperature to obtain an active solid waste-based powder as a carrier material; (3) taking the phase change material and placing it in an experimental container for water bath heating, maintaining the temperature at 60°C, and then using magnetic stirring until the phase change material is completely melted; (4) introducing the melted phase change material in step (3) into the active solid waste-based powder container in step (2), mixing, and vacuum impregnating in a vacuum drying oven, maintaining an environment of 1 Pa and a temperature of 60° C., and impregnating for 4-6 hours; (5) placing the mixture in (4) in a shearing device, stirring at a speed of 150 r / min for 5-10 minutes, adding the shell material three times, and continuing to stir for 10 minutes; (6) The mixture in (5) is placed in a drying oven and dried for 2-4 hours, and sheared into particles using a shearing machine with a fineness of 10-20 mesh, thereby obtaining a polymer-coated solid waste-based phase change material.

5. An application of the polymer-coated solid waste-based phase change material according to any one of claims 1 to 3 in temperature self-regulating asphalt, characterized in that: A temperature self-regulating asphalt is prepared by mixing a polymer-coated solid waste-based phase change material with a dispersant and petroleum asphalt in a weight ratio of (5-20):(0.4-0.9):

100.

6. The use of a polymer-coated solid waste-based phase change material in temperature self-regulating asphalt according to claim 5, characterized in that: The petroleum asphalt is 70# petroleum asphalt.

7. The use of a polymer-coated solid waste-based phase change material in temperature self-regulating asphalt according to claim 5, characterized in that: The dispersant is any one of polyvinyl alcohol, fatty alcohol polyoxyethylene ether and polyoxyethylene.

8. The use of a polymer-coated solid waste-based phase change material in temperature self-regulating asphalt according to claim 5, characterized in that: The preparation of temperature self-regulating asphalt includes the following steps: S1. Heat petroleum asphalt to 130-150℃ until it melts; S2, introduce the petroleum asphalt in S1 into the shearing device and stir at a speed of 200r / min for 3-5 minutes; S3, add the dispersant into the shearing device, maintain 130-150°C, and stir at a speed of 200r / min for 10 minutes; S4. Add the polymer-coated solid waste-based phase change material into the dispersant of S3, and continue stirring at a speed of 400 r / min for 15-20 minutes to obtain a temperature self-regulating asphalt.

Citation Information

Patent Citations

  • Powdery diatomite composite phase-change material and preparation method thereof

    CN102746824A

  • Preparation method of blast furnace slag-based composite phase-change heat storage material

    CN107099275A

  • Red mud-paraffin composite phase-change energy storage material and mixed grinding preparation method thereof

    CN107286913A

  • Temperature-control high-performance solid waste asphalt concrete

    CN113024160A

  • Composite phase-change temperature-regulating material for asphalt pavement and preparation method of composite phase-change temperature-regulating material

    CN114276039A